The Qur’anic Learning Methods for Primary School Pupil in Indonesia: A Systematic Literature Review - Muttaqin, Sopian Kamil; Asshdiqi, Ahmad Fajri; Rizki, Aulia (Journal of Education Method and Learning Strategy, 2025)
This study aims to elucidate the various methods employed in teaching the Qur’an in Indonesian primary schools. Previous studies predominantly focused on Qur’anic memorization methods among secondary school students in Indonesia. This research adopts the Systematic Literature Review (SLR) methodology, which analyzes journal articles published between 2019 and 2024. Following a rigorous screening process by PRISMA, eleven relevant articles were identified. The findings reveal that the most frequently utilized methods in Qur’anic instruction are the Ummi and Qiro’ati, while other approaches, such as Wafa, Tajdied, Wahdah, FLASH, Demonstrasi, and Klasikal, are employed to a lesser extent. Data collection techniques predominantly include observations, questionnaires, and documentation. Furthermore, Juz ‘Amma is the most commonly used section of the Qur’an in elementary school instruction. This study enhances Islamic education, particularly in Qur’anic studies at the primary school level, by fostering a generation that internalizes and upholds Qur’anic values in both contemporary and future contexts.